Bridging Revolutionary Legacy and Contemporary Practice: Li Dazhao's Philosophy of Youth Education and Its Relevance for Cultivating New-Era Talent - Qing Zhang; Fuhai Xia (Ilmu Inovasi Nusantara, 2025)
The intellectual and moral cultivation of youth has become an urgent challenge in the context of rapid globalization, technological disruption, and cultural transformation. Contemporary education often struggles to balance theoretical knowledge, social responsibility, and holistic personality development, leading to fragmented growth among young learners. Against this backdrop, the pioneering contributions of Li Dazhao (1889–1927), one of the earliest disseminators of Marxism in China, offer valuable insights. His educational philosophy—developed through revolutionary praxis and philosophical synthesis—remains highly relevant for addressing the current dilemmas of youth education. This study aims to examine Li Dazhao's tripartite educational framework: theoretical arming, responsibility cultivation, and holistic personality development, and to explore its applicability in constructing a new paradigm of youth education for socialist modernization. Methodologically, the research employs a qualitative approach through historical analysis and textual interpretation of Li's writings, including My View on Marxism and related works, while also engaging with secondary scholarship on Marxist education and Chinese intellectual history. The findings highlight that Li Dazhao successfully integrated Marxist theory with traditional Chinese humanism and experiential pedagogy, thereby cultivating youth who were both ideologically committed and socially engaged. His emphasis on linking theory with practice, responsibility to the nation, and personality formation provides a systematic model for contemporary youth development. The implications of this study suggest that Li's framework can inform the design of modern ideological and political education, the promotion of civic responsibility, and the construction of personality education systems that respect individual diversity. Ultimately, his vision contributes to cultivating ethically grounded, socially responsible, and historically conscious youth capable of meeting the challenges of the new era